How real is the long-lasting effect of tumor necrosis factor α inhibitors? Focus on immunogenicity - D.E. Karateev (Современная ревматология, 2014)
Tumor necrosis factor (TNF) α inhibitors are the most commonly used agents to treat rheumatoid arthritis (RA) and other inflammatory arthropathies. Five drugs belonging to the family of TNFα inhibitors have been certified in Russia for treating RA: infliximab (INF), adali- mumab (ADA), golimumab, certolizumab pegol, and etanercept (ETN). These drugs have different compositions. ETN does not belong to the family of monoclonal antibodies (mAbs) and has a different mechanism of action. It is a dimeric molecule of synthetic fusion protein contain- ing TNF receptor and bound to the Fc-fragment of human Ig1. ETN can inhibit both TNFα and lymphotoxin α. ETN contains only the pro- tein identical to human protein. All TNFα inhibitors exhibit a virtually identical anti-inflammatory activity. The data from the registries show that the risk of discontinuation of therapy with TNFα during the first 2–3 years is appreciably high; there is a trend toward increased frequency of therapy discontinuation because of loss of effectiveness. It was found that the risk of therapy discontinuation because of insufficient effectiveness and adverse events (AEs) is minimal for ETN and maximal for INF. The structure of biological drugs (which also affects their immunogenicity) has the key neg- ative effect on maintaining the response to therapy and frequency of AEs. However, since ETN is a fusion molecule and contains less poten- tially immunogenic epitopes compared to mAbs, the frequency of detecting anti-drug antibodies (ADAbs) is appreciably lower. The fact that ETN has a lower immunogenicity can be used to explain the significantly lower probability of discontinuing therapy using this drug as compared to INF and ADA. The risk that the need to increase the dose because of gradual loss of effectiveness of therapy with ADA and INF, was 4.9- and 28-fold higher, respectively, as compared to ETN. Therapeutic algorithms make it possible to control therapy with TGFα inhibitors (development of ADAbs, blood concentration of drug), as well as to switch to using another biological drug. Currently, the main method for preventing ADAb formation is to strictly follow the recommenda- tions for using biological drugs in combination of disease-modifying anti-rheumatic drugs (first of all, with methotrexate). TNFα inhibitors hav- ing the lowest immunogenicity (ETN, etc.) are advisable to be used in this case.